Analisis Kuersetin dan Rutin pada Ekstrak Krokot (Portulaca oleraceae L.) dan Ekstrak Pare (Momordica charantia L.) secara KCKT: Analysis of Quercetin and Rutin in Krokot (Portulaca oleraceae L.) Extract and Pare (Momordica charantia L.) Extract by HPLC - Sari, Anggya Shinta Etika; Syaira, Dear; Dhurhania, Crescentiana Emy; Susilowati (Program Studi Farmasi-Fakultas Matematika dan Ilmu Pengetahuan Alam-Universitas Tulang Bawang, 2024)
Krokot (Portulaca oleraceae L.) and Pare (Momordica charantia L.) are plants containing flavonoid compounds of quercetin and rutin. The purpose of this study is to know quercetin levels and rutin in the krokot and pare established by high performance liquid chromatography (HPLC) and to know the acceptance of linearity test requirements. Krokot extraction uses soxhletation techniques with ethanol 96% while pare uses maseration techniques with ethanol 70%. The viscous extract is used for the quercetin and rutin compound concentrations by HPLC using stationary phase is C18, mobile phase is methanol : phospat acid 0,1% (70:30), flow rate of 1 ml/min and the length of the detection at 371 nm wavelength. The result of quercetin compound of krokot gets 0.019 % and the rutin compound 0.042 % while its quercetin compound of pare extract is 0.028 % and the rutin compound 0.037 %. The results of the linearity test of quercetin and rutin compounds obtained a correlation coefficient value of 0.99 so that it meets the requirements for a good linearity test. Keywords: Quercetin, Rutin, Krokot, Pare, HPLC